The Correlation between Grammar Mastery and Basic English Speaking Skills: A Case of Beginners at AGNES Course Kediri - Maylizza Zuyyina Rizqy Fadila; Hartono Hartono (Journal of Advanced Multidisciplinary Research, 2026)
Grammar mastery plays a significant role in helping learners produce clear and fluent spoken English. This study explored the correlation between grammar mastery and basic English speaking skills among beginners at AGNES English Course in Kediri. Although these learners frequently encounter English through games, music, and social media, many learners still experience difficulties in speaking confidently, especially in formal situations. Limited grammar mastery can contribute to unclear or fragmented speech, making communication less effective and reducing students’ confidence. Using a quantitative approach with a descriptive correlational design, this study involved 30 beginners who were selected through purposive sampling. Data were collected using a grammar test and a speaking task, and were analyzed using Pearson’s Product-Moment Correlation to examine whether grammar mastery was related to speaking skills. The study aimed to provide practical insights into how grammar supports clear and fluent speaking. The results showed a moderate and statistically significant positive correlation between grammar mastery and basic English speaking skills (r = 0.537, p < .01), indicating that learners with higher grammar mastery tended to demonstrate better speaking performance. These findings suggest that grammar mastery plays an important role in supporting beginners’ speaking development. Therefore, integrating grammar instruction into speaking activities is recommended to help learners speak more clearly and confidently in both informal and formal situations.